2016
DOI: 10.1159/000452333
|View full text |Cite
|
Sign up to set email alerts
|

Early Intervention Improves Clinical Responses to House Dust Mite Immunotherapy in Allergic Rhinitis Patients

Abstract: Background: Allergen immunotherapy (AIT) is the unique causal treatment for respiratory allergy. As AIT is expensive and of long duration, the availability of a marker predicting AIT responders is of crucial relevance. Objective: To investigate clinical parameters correlated with effective AIT in allergic rhinitis (AR) patients. Methods: This is a prospective, nonrandomized open study in which a total of 284 AR patients who had received house dust mite (HDM) subcutaneous AIT were enrolled from January 2011 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…The symptoms and medication use were significantly improved after 1 year of AIT with the 2 HDM extracts. The efficacy of AIT could be observed at 3 months and the CSMS scores decreased consecutively at 6, 9, and 12 months, which was consistent with previous studies . Our study implied that the subcutaneous immunotherapy had an early effect on AR symptoms.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The symptoms and medication use were significantly improved after 1 year of AIT with the 2 HDM extracts. The efficacy of AIT could be observed at 3 months and the CSMS scores decreased consecutively at 6, 9, and 12 months, which was consistent with previous studies . Our study implied that the subcutaneous immunotherapy had an early effect on AR symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…Sample size was calculated using non‐inferiority test with a 1‐sided 0.05 significance level and a 13% delta. The effective percentage of Alutard SQ and NHD HDM CSMS reduction was 69.7% and 71.3% in previous studies; it was calculated that 196 patients (98 per group) were required to achieve a power of 80%.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…Allergic rhinitis (AR) is the most common allergic disease and affects 10-40% of the population worldwide [1]. In China, self-reported AR in the general adult population significantly increased over a 6-year period [2].…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that the concentration of HDM allergens in the bedroom during early life is significantly associated with sensitization to HDM allergens [4]. Importantly, early intervention by allergen-specific immunotherapy significantly improved the clinical response to HDM allergens in a nonrandomized open study [5]. These reports suggest that the avoidance of airborne allergens achieved by controlling the local environment and optimal treatment during early life may be important in preventing future allergen sensitization and the crisis of allergic asthma.…”
Section: Introductionmentioning
confidence: 99%